A kisvállalkozások növekedésének korlátai (Szociológiai Szemle, 2024)
The paper analyses the limitations of the numerical growth of small (micro) enterprises that have been founded extensively in Hungary. It shows that this stratum of small entrepreneurs (self-employment) is traditionally based on the labour of the family and does not wish to employ outside labour, or if yes. only to a very limited extent.